1989
DOI: 10.1111/j.1365-2621.1989.tb05179.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of the Sweetener Sucralose

Abstract: The physicochemical properties of the high intensity sweetener, sucralose, (1,6-dichloro-1,6-dideoxy+D-fructofuranosyl 4-chloro-4-deoxy-cY-D-galactopyranoside) were determined. A high solubility in water (2&3g/lOO mL at 20°C) in combination with Newtonian viscosity characteristics, a negligible lowering of surface tension, and no pH effects demonstrated that sucralose was particularly suitable for use in liquid products. The refractive index of aqueous solutions was linear with respect to concentration confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…It was due to the loss in bulk that corresponded to the decrease in amount of sugar. Jenner and Smithson (1989) found viscosities of sucrose and sucralose solutions of same concentrations to be comparable. Thus, when sucralose was added to replace sugar in the milk at an equi-sweet level, very low amount was used and thus viscosity of the samples declined.…”
Section: Resultsmentioning
confidence: 81%
“…It was due to the loss in bulk that corresponded to the decrease in amount of sugar. Jenner and Smithson (1989) found viscosities of sucrose and sucralose solutions of same concentrations to be comparable. Thus, when sucralose was added to replace sugar in the milk at an equi-sweet level, very low amount was used and thus viscosity of the samples declined.…”
Section: Resultsmentioning
confidence: 81%
“…The latter observation indicates significant attenuation of sucralose at depth in the groundwater, under suboxic to anoxic conditions, given that groundwater at these depths has consistently had very low dissolved oxygen concentrations (<1 mg/L, Robertson et al, 2011). Sucralose is a hydrophilic nonionic compound: the reported n-octanol/ water partitioning coefficient (P ow ) is low (log P ow = −0.51: Jenner and Smithson, 1989), and its tendency to sorb to solid phases in the subsurface is inferred to be weak to negligible, as recently demonstrated in laboratory tests with silt loam and peat soils by Soh et al (2011), who observed significantly less sorption of sucralsoe than acesulfame. Accordingly, the observed attenuation of sucralose at depth in the plume at Long Point is likely due to biodegradation.…”
Section: Evidence For Attenuation Of Sucralose In the Plumementioning
confidence: 99%
“…WWTPs use a combination of physical, chemical, and biological treatment processes to remove organic substances from water. Due to its low K OW ¼ 0.3 ( Jenner and Smithson, 1989), sucralose is very hydrophilic; hence, it is not predicted to be removed by sorption to and settling of wastewater biomass. Therefore, removal of sucralose from wastewater requires chemical (through the disinfection process) or biological (anaerobic or aerobic) treatment.…”
Section: Introductionmentioning
confidence: 99%